Proses Penerimaan Diri Mahasiswa yang mengalami Pelecehan Seksual di Kampus (Jurnal Ilmiah Psikologi MIND SET, 2025)
Sexual harassment is a form of gender‑based violence that can lead to significant psychological impacts, including low self-esteem, trauma, and behavioral changes. This study aims to explore the process of self-acceptance among university students who experienced sexual harassment on campus. A qualitative approach with a single case study design was employed, using in-depth interviews as the data collection method. The findings reveal that the survivor experienced severe psychological distress, such as suicidal thoughts, social withdrawal, and academic disruption. The self-acceptance process was supported by peer support and increased religiosity, which helped the survivor recover and reduce harmful behaviors. This study highlights the importance of social and spiritual support in the healing process of sexual violence survivors.